Hard candy - Slade, David; Wilson, Patrick, 1973-; Page, Ellen; Oh, Sandra, 1971-; Vulcan Productions; Lions Gate Home Entertainment (Santa Monica, CA : Lions Gate Home Entertainment, 2006)
A teenage girl hooks up with a 30-something fashion photographer she met on the Internet. She soon proves that she isn't as innocent as she looks. The night takes a turn when she imposes an investigation in an attempt to reveal his past.
Title from container.
Originally released as a motion picture in 2005.
Special features: Commentary with director David Slade and writer Brian Nelson; Audio commentary with actors Patrick Wilson and Ellen Page; Deleted and extended scenes; Making -of documentary; "Controversial confection: the soul of 'Hard candy'" featurette; DVD-ROM production notebook.
Director of photography, Jo Willems ; editor, Art Jones ; music, Molly Nyman, Harry Escott.
Patrick Wilson, Ellen Page, Sandra Oh, Odessa Rae.
MPAA rating: R; for disturbing violent and aberrant sexual content involving a teen, and for language.
Keywords: Online dating -- Drama; Criminal behavior -- Drama; Feature films; Films for the hearing impaired; Thriller -- Feature; Youth -- Feature; Crime -- Feature; Suspense films